A PHYTOCHEMICAL STUDY OF SPECIES COLLECTED IN THE CAATINGA WITH ANTICHOLINESTERASE PROPERTIES - V. T. N DE A. E CASTRO,; A. J. C. CORREA,; B. DE A. ANDRADE,; G. G. DE OLIVEIRA,; N. P. LOPES,; T. A. S. ARAÚJO,; T. J. S. PEIXOTO SOBRINHO,; E. L. C. DE AMORIM, (International Journal of Pharma and Bio Sciences, 2016)
The cholinergic explanation of the clinical manifestations of Alzheimer’s disease (AD) is one of the most widely accepted hypotheses, leading to the use in treatment of substances that are capable of increasing levels of the neurotransmitter acetylcholine (ACh) in the brain, such as acetylcholinesterase enzyme (AchE) inhibitors. However, the substances available on the market are relatively toxic and have side-effects and research into natural products is an alternative way of seeking out new products for this purpose. Citrus limonum, Ricinus communis and Senna occidentalis have produced promising results for anticholinesterase properties. The aim of the present study was to produce a phytochemical characterization of the components present in extracts of these three species, with a view to guiding the search for compounds that are promising candidates for treatment of AD. CG-MS analysis was conducted of 36 compounds selected according to the study’s inclusion criteria, including simple and more complex substances, such as coumarins, terpenoids and their derivatives, with known anticholinesterase properties, demonstrating the wealth of substances present in various promising species of plant, with a special emphasis of the search for bioactive compounds.